Comparação entre teletrabalho e trabalho presencial: percepção de trabalhadores de empresas do ramo de serviços - Gasques, Mateus de Oliveira (Universidade Federal de São Carlos, 2021)
The advancement of technology has helped to make work more flexible, promoting structural changes in the way it has been performed. In this context, teleworking or home office is emerging as a strong global trend, expanding the spatial and temporal limits of organizations. We sought to understand, in this research, which are the practical and subjective effects that guide the perceptions of professionals who adhere to this work regime. Based on the experiences shared by teleworkers in the service sector, the study considered the main elements that define the personal perception of this work and compared them with what is experienced in face-to-face work. The case study was developed from semi-structured interviews, applied to 10 workers from different companies in the service sector. Based on the results, it is possible to understand a dual character of each factor that promotes the perception of this type of professional and a general preference of the interviewees for the adhesion of hybrid work regimes. The results allowed to conclude that the success in adhering to this work format is linked to the profile of both the professional and the employer.
Comparison between telework and on-site work: perception of workers in service companies
Keywords: Teletrabalho; Home office; Estudo do trabalho; Ergonomia da atividade; Ergonomia; Telecommuting; Work study; Activity Ergonomics; Ergonomics; ENGENHARIAS::ENGENHARIA DE PRODUCAO; ENGENHARIAS